2022
DOI: 10.1136/bmjopen-2021-060512
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot of health-related behaviours in adults living with disabilities 1 year into the COVID-19 pandemic: a cross-sectional survey study

Abstract: ObjectivesThis survey aimed to assess the status of a range of health-related behaviours 1 year after the coronavirus outbreak was declared a pandemic in adults living with disabilities comparative with those with no disabilities.DesignThis cross-sectional study reports findings from an online survey conducted in March 2021. Mann-Whitney U and Χ2 tests were used to compare a range of health behaviours including time spent self-isolating, smoking, alcohol consumption, exercise frequency and diet in adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…We found large differences in PA levels between Canadian and Dutch participants (163 min vs. 934 min of PA). PA levels of the Canadian participants were generally low, but comparable to findings from other studies on measured self-reported PA among people with physical disabilities [9,10,13,45]. In contrast, PA levels of Dutch participants were high compared to other Dutch studies on self-reported PA among people with physical disabilities and/or chronic diseases [46][47][48].…”
Section: Physical Activitysupporting
confidence: 75%
See 4 more Smart Citations
“…We found large differences in PA levels between Canadian and Dutch participants (163 min vs. 934 min of PA). PA levels of the Canadian participants were generally low, but comparable to findings from other studies on measured self-reported PA among people with physical disabilities [9,10,13,45]. In contrast, PA levels of Dutch participants were high compared to other Dutch studies on self-reported PA among people with physical disabilities and/or chronic diseases [46][47][48].…”
Section: Physical Activitysupporting
confidence: 75%
“…Although the prevalence of increased alcohol consumption during the pandemic was lower in our samples, the percentage of participants reporting to have increased their alcohol consumption during the pandemic is still worrisome. They do partly overlap with findings from the UK [45] and emphasize the need to develop multiple lifestyle programs and interventions to support PWD, but also people without disabilities in starting and maintaining a healthy lifestyle during and after the pandemic.…”
Section: General Health Mental Health and Lifestylementioning
confidence: 67%
See 3 more Smart Citations